Real-time monitoring wildlife using autopilot quadcopter with Wi-Fi facility (camera trapping and router extender) / Mohamad Shahafizul Abdullah @ Aziz - Abdullah @ Aziz, Mohamad Shahafizul (2016)
From the THE STAR newspaper 14th April 2015, at least five of Malaysia's mammal species, including the Sumatran Serow, dugong and the Malayan tiger are now facing extinction [1], This is due to human activities such as logging, over-development and poaching [1]. In Malaysia, there are no advance system or method that can monitor the wildlife more efficient and effectively. Some conventional methods include surveys on the footprints, dung, calls, live trapping, den counts and direct observation [2]. The problem of these methods, there are no technologies on wildlife monitoring system that can visually monitor during real-time on illegal activities in remote locations [3]. On top of that, the information need to be informed quickly when illegal incidents occurred in the forest so that the relevant authorities can be assigned to stop the illegal activity. The objectives of this projects is to design a system for real-time monitoring using smartphone application, to develop a system that can provide WI-FI signal at any place in the forest for faster data collection and to design the night vision monitoring system and to extend the WI-FI signal coverage. This project is a real-time monitoring wildlife which uses an autopilot quadcopter and provides WI-FI facility for the forest rangers or to the jungle trekkers. The design implementation that are carried out is by applying Monitoring tools using high definition camera with WI-FI supported and night vision capable and Global Positioning System(GPS). The system is capable to improve the monitoring work in the jungle and also improves care control on wildlife effectively. This project will be beneficial to the Wildlife Conservation Society as to monitor the wildlife in large area during real time and provide WI-FI facilities for the forest rangers and jungle tracker